Analisis Bias Gender Dalam Iklan Super Pell - Muhammad Eko Riyadi; Rini Sulastri (UIN Sunan Gunung Djati Bandung, 2024)
The media in its development has its own influence on people's point of view. Likewise, gender issues are also part of the media scheme itself. This article discusses gender issues, namely gender bias in the advertising media for the television show